Preliminary study on low-density polystyrene microplastics bead removal from drinking water by coagulation-flocculation and sedimentation - Li, Chaoran; Busquets, Rosa; Moruzzi, Rodrigo B. [UNESP]; Campos, Luiza C. (Elsevier, 2021)
Microplastics (MPs), sized ~150 μm, have been found in tap water at levels of ~5 particles/L, suggesting that water treatment plants are not effectively removing MPs. Therefore, there is an urgent need to evaluate their fate in drinking water treatment processes. Coagulation-flocculation and sedimentation are applied in water treatment to primarily decrease turbidity, and MPs contribute to water turbidity. This study focuses on the removal of polystyrene (PS) beads of 100 μm with density 1.04–1.06 g/cm3. The low-density PS beads pose a removal challenge because they have similar density to the media. The effects of initial water pH and stirring speed on MPs removal by coagulation-flocculation and sedimentation were studied. The most effective conditions found for removing the PS beads from water, that led to removal rates up to 98.9 ± 0.94%, were 3.4 mg Al/L of coagulant, pH 5, flocculation time of 7 min and sedimentation time of 30 min. For the first time, floc breakage and regrowth following the addition of Al, has shown to favour the removal of the PS beads. Based on this research, coagulation-flocculation can play a very important role in removing MPs during drinking water treatment.
Keywords: Aluminium sulphate; Floc breakage; Microbead; Polystyrene; Water treatment